Pengembangan Audiovisual Pembuatan Starter Kompos Sampah Basah Kulit Mangga untuk Melatih Literasi Teknologi dan Literasi Lingkungan - Rofiqi, Ainur; Sumberartha, I Wayan; Al Muhdhar, Mimien Henie Irawati; Utami, Amrih (Universitas Negeri Surabaya, 2025)
The purpose of this study is to produce audiovisual media for making mango peel wet waste composting starter to train valid and practical technological literacy and environmental literacy. The research method uses the Lee & Owens (2004) development model and adopts several stages from Branch (2009). The media developed was declared valid by material and media experts through validation tests and declared practical by biology education practitioners and student responses. The results of the study are known that validation tests by material and media experts are classified as very valid (100%), biology education practitioners are very practical (100%), and student responses are also very practical including one to one trial (91%), small group trial (90%), field trial (92%), and conduct a pilot test (93%). The conclusion of this study is known that the audiovisual media developed are very valid and very practical so that they can be applied in learning.